Synthesis of 7,2′-Dihydroxy-4′,5′-Dimethoxyisoflavanone, a Phytoestrogen with Derma Papilla Cell Proliferative Activity - Kim, Taewoo; Kim, Hyun Su; Jang, Jaebong; Kim, Dong Jun; Lee, Jongkook; Lee, Dongjoo; Kim, Seok Ho (Molecules, 2022)
This paper reports a concise and scalable method for the synthesis of the phytoestrogen 7,2′-dihydroxy-4′,5′-dimethoxyisoflavanone 1 via an optimized synthetic route. Compound 1 was readily obtained in 11 steps and 11% overall yield on a gram scale from commercially available 3,4-dimethoxyphenol. The key features of the synthesis include the construction of the deoxybenzoin unit through a sequence of Claisen rearrangement, oxidative cleavage, and aryllithium addition and the efficient synthesis of the isoflavanone architecture from highly functionalized 2-hydroxyketone.
Keywords: Phytoestrogens; Stereoisomerism; Dalbergia oliveri; deoxybenzoin; hair growth; isoflavanone; phytoestrogen; total synthesis